Impact of the manufacturing sector on the export competitiveness of European countries: A spatial panel analysis - Aleksandra Kordalska; Magdalena Olczyk (Comparative Economic Research. Central and Eastern Europe, 2014)
The purpose of this paper is to determine how changes in the export competitiveness of the EU economy (measured by exports and net exports) depend on changes in the competitiveness of processing industries, on the basis of manufacturing data from 19 EU countries over years 1995-2009 and using a spatial panel data model. The determinants of export competitiveness are selected in the light of predictions from international trade theory, growth theory and the theory of innovation. In particular, the paper explores how the size of foreign demand, the value of domestic demand, the level of ULC in the sector, the degree of openness of the sector to foreign markets, labour productivity and intermediate consumption in a sector affect the export competitiveness of the European economies selected. The results from spatial data models lead to a conclusion about the statistical significance of spatial dependencies in export competitiveness modelling. The analysis indicates the different determinants of export competitiveness, both if it is measured by export value and if it measured by net exports. The authors hope that the results will be a voice in the discussion on enhancing the competitiveness of European industrial sectors
Keywords: 330; international trade; export competitiveness; manufacturing; spatial data model; European Union